MENGGABUNGKAN COMPETING VALUES FRAMEWORK DAN KETERBUKAAN INFORMASI PERUSAHAAN UNTUK MENILAI KEEFEKTIFAN ORGANISASIONAL - Purwoto, Lukas (Benefit, 2006)
The issue of organizational effectiveness has been one of the most important research subjects sincethe early development of organizational theory. One model widely known in the study of organizationaleffectiveness is competing values framework. Besides that, it is also known that annual report providesinformation to the stakeholders. In order to evaluate organizational effectiveness, this paper discussesthat corporate disclosure could serve as data source to measure many criteria of competing values framework. Apparently, this corporate disclosure based competing values framework is appropriatefor both of the early and the end of organization life cycle. The quantity and quality of disclosures also determine the success of its implementation